Audio coding for the wireless channel - Ng, Wei Keng. (2008)
In this report, an audio codec for the wireless channel is proposed. It deploys wavelet packet transform, which has better time and frequency localization compares to other transforms such as Fourier transform, Modified Discrete Cosine Transorm, and etc.